Accountable Care Organizations and Otolaryngology. (4th June 2015) - Contrera, Kevin J.; Ishii, Lisa E.; Setzen, Gavin; Berkowitz, Scott A.
Abstract : Accountable care organizations represent a shift in health care delivery while providing a significant potential for improved quality and coordination of care across multiple settings. Otolaryngologists have an opportunity to become leaders in this expanding arena. However, the field of otolaryngology–head and neck surgery currently lacks many of the tools necessary to implement value‐based care, including performance measurement, electronic health infrastructure, and data management. These resources will become increasingly important for surgical specialists to be active participants in population health. This article reviews the fundamental issues that otolaryngologists should consider when pursuing new roles in accountable care organizations.